Transcriptome Profiles of Strawberry (Fragaria vesca) Fruit Interacting With Botrytis cinerea at Different Ripening Stages - Haile, Zeraye Mehari; Nagpala-De Guzman, Ellaine Grace; Moretto, Marco; Sonego, Paolo; Engelen, Kristof; Zoli, Lisa; Moser, Claudio; Baraldi, Elena (Frontiers in Plant Science, 2019)
Gray mold caused by Botrytis cinerea is a major cause of economic losses in strawberry fruit production, limiting fruit shelf life and commercialization. When the fungus infects Fragaria x ananassa strawberry at flowering or unripe fruit stages, symptoms develop after an extended latent phase on ripe fruits before or after harvesting. To elucidate the growth kinetics of B. cinerea on flower/fruit and the molecular responses associated with low susceptibility of unripe fruit stages, woodland strawberry Fragaria vesca flowers and fruits, at unripe white and ripe red stages, were inoculated with B. cinerea. Quantification of fungal genomic DNA within 72 hours post inoculation (hpi) showed limited fungal growth on open flower and white fruit, while on red fruit the growth was exponential starting from 24 hpi and sporulation was observed within 48 hpi. RNA sequencing applied to white and red fruit at 24 hpi, showed that a total of 2141 genes (12.5% of the total expressed genes) were differentially expressed due to B. cinerea infection. A broad transcriptional reprogramming was observed in both unripe and ripe fruits, involving in particular receptor and signaling, secondary metabolites, and defense response pathways. Membrane-localized receptor-like kinases and nucleotide-binding site leucine-rich repeat genes were predominant in the surveillance system of the fruits, most of them being downregulated in white fruits and upregulated in red fruits. In general, unripe fruits exhibited a stronger defense response than red fruits. Genes encoding for pathogenesis-related proteins and flavonoid polyphenols as well as genes involved in cell-wall strengthening were upregulated, while cell-softening genes appeared to be switched off. As a result, B. cinerea remained quiescent in white fruits while it was able to colonize ripe red fruits.